PUBLIC RELATIONS STRATEGY OF THE V HELVETIA FIRE DEPARTMENT IN IMPROVING THE INSTITUTION'S IMAGE IN THE COMMUNITY - Bayu Febrian Alfarabi; Nurhanifah Nurhanifah (Program Pascasarjana UIN Sumatera Utara, 2026)
This study aims to analyze the public relations strategies implemented by Helvetia Fire and Rescue Service Unit V to enhance the institution’s public image, examine the communication program planning process, and evaluate the mechanisms used to address public complaints. The study employed a qualitative approach using a descriptive qualitative method. Data were collected through in-depth interviews with institutional leaders, public relations staff, and community members, supported by observation and documentation. Data analysis involved data reduction, data display, and conclusion drawing, while data validity was ensured through source and methodological triangulation. The findings indicate that the public relations strategies of Helvetia Fire and Rescue Service Unit V successfully fostered positive public perceptions and strengthened public trust through rapid emergency response and communicative, free educational programs. Communication program planning was oriented toward the actual needs of the community, employed accessible language, and utilized a media-mix approach. In addition, the evaluation process was conducted transparently by treating public criticism as constructive input for the continuous improvement of operational performance. The study concludes that adaptive and responsive two-way communication is a key factor in maintaining accountable public service quality and strengthening the institution’s positive image